Crescimento vegetativo, produção e composição químico-bromatológica da palma forrageira consorciada com cajá (Spondias spp) - Peixoto, Márcio José Alves (2009)
In the Brazilian Northeast the efficiency of the animal production was increased when combining native pastures and grass adapted in consequence of the low productivity of the native grass, mainly at that time of drought. The importance of the forager palm as one of the most important grass, for your high productivity and quality for the ruminant. However, this research had the objective to evaluate the vegetative growth, production and composition chemistry-bromatologic of the joined forager palm with caja (Spondias spp) in the semi-arid person from the state of Ceará. The experiment was led in the Experimental Farm, in Quixadá, CE in the period from 2003 to 2007, with the planting accomplished in November of 2003 in soil classified like texture Luvissolo Sandy Franco. The experimental desig was randomly blocks with factorial by 2x2x2 with 4 repetitions, with the following treatments: T1 - Plant Sun Not Fertilized east/weast; T2 - Planting Fertilized Sun east/weast; T3 - Plant Sun Not Fertilized Noth/South; T4 - Planting Fertilized Sun North/South; T5 - Plant Shadow Not Fertilized east/weast; T6 - Plant Shandow Fertilized east/weast; T7 - Plant Shandow Not Fertilized North/South; T8 - Plant Shandow Fertilized North/South. In the treatments with manuring 1 kg/cov of tanned bovine manure was placed, corresponding to 20 t / ha. The plant used for the shandow it was the caja (Spondias ssp.), spaced of 7 x 7 m and cup with 1.5 m of height. To accomplish the measures morphometric length, width and thickness used a ruler of 50 cm and a caliper, respectively. During the collection of each plant the cladodes were numbered by order, being the primary cladodes those original of the cladode base, the secondary ones those original of first order and so forth and heavy. Soon after a composed sample was removed to determine the tenors of Fiber in Acid Detergent, Lignina, Ethereal Extract, Crude Protein, ash. For the appraised parameters a variance analysis was accomplished to verify the significant of the factors (sun and shade, east/weast and north/south, fertilized and not fertilized and the interaction among the factors) and the averages compared by the test of Tukey to 5% of probability. Significant effect was verified (P<0.05) for interaction sun/shade and fertilized/not fertilized for the variable length, width, thickness of the cladodes, productivity of the forager palm, ash and total carbohydrates. Already for the Fiber in Acid Detergent verified significant effect (P<0.05) for the interaction sun/shandow and east/weast, north/south. Conclude that in the edafoclimatic conditions where the experiment was lead, the organic fertilization and the plantation in the sun they induce to one better performance of the forager palm (Opuntia fícus-indica (L.) Mill).